Embodied Narratives Protecting Identity Interests through Ethical Governance of Bioinformation - Postan, Emily (Social Sciences, 2022)
As increasing quantities of health and biological information are generated, the need for us all to consider the human impacts of its ubiquity becomes more urgent than ever. This book explains the ethical imperative to take seriously the potential impacts on our identities of encountering bioinformation about ourselves.